On the features of 4D gravity monitoring of the geological environment - Yu. I. Dubovenko; O. A. Chernaya (Геофизический журнал, 2011)
A notion and peculiarities of 4D gravity monitoring are defined. Its data processing on the short profiles is suggested to execute by the given expressions with fast decaying cores, and gravity fluctuations due to impact of low-intensity geophysical factors should be taken into account by the Dvulit's techniques.